Spiritual Needs Questionnaire (SpNQ): Validity Evidence among HIV+ Patients in Northeast Brazil - Oliveira da Silva, Cassiano Augusto (Religions, 2020)
The Spiritual Needs Questionnaire (SpNQ) measures psychosocial, existential, and spiritual needs in clinical contexts. The objective was to confirm its factor structure in Brazil, comparing the results of its validation for Portuguese in Rio de Janeiro, under similar sampling conditions, in João Pessoa (Paraíba-Brazil), among 157 HIV(Human Immunodeficiency Virus)+ patients, most of them men (49%) (women = 35%; other = 16%), aged between 30 and 49 years (53.5%). From exploratory factor analysis and internal consistency analysis a structure of five factors (or components) was obtained: Religious Needs (α = 0.73), Inner Peace and Family Support Needs, gathered (α = 0.64), Existential Needs (α = 0.49) and two new factors instead of “Giving/Generativity Needs”, being Social Recognition Needs (α = 0.54), referring explicitly to religious practices, with items formerly found in the Religious Needs factor, and Time Domain: Reflection and Clarification Needs (α = 0.57), which group only two items (item 4, “reflection on the past” (formerly in the Inner Peace component) and item 5, “resolution of outstanding problems”). The institutional religiosity perceived in the composition of the Social Recognition Needs component shows that these patients differentiate “religiosity” from “spirituality”. The Religious Needs component was formed with items from the “spirituality” construct definition. The most important component was Inner Peace and Family Support Needs, a relevant coping strategy in this disease. The results met proper validity criteria, and SpNQ proved to be sensitive and appropriate to situations of cultural and clinical diversity between samplings.